2020
DOI: 10.1080/22423982.2020.1799676
|View full text |Cite
|
Sign up to set email alerts
|

Piecing together the Labrador Inuit food security policy puzzle in Nunatsiavut, Labrador (Canada): a scoping review

Abstract: Inuit in Canada experience greater social and economic inequities than the general Canadian population. Food security exemplifies this inequity and is a distinct determinant of Inuit health. This scoping review focuses on food security-related policies implemented in Nunatsiavut, located in Northern Labrador. The primary objective was to identify the range of existing policies that pertain to food security in Nunatsiavut. The secondary objective was to complete a directed content analysis to map each policy ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Food security and nutrition are major concerns in Nunatsiavut communities. As noted by Bowers et al (2020), a 2014 study found that 59.3% of the population was food insecure, while in the same year the same measurement Canadawide was 22%. According to Participant 8, some of the char bought by the Nunatsiavut Government is also traded with fishers in southern Labrador for Atlantic cod, which gives the community freezer program some variety.…”
Section: Food Security and Food Sovereigntymentioning
confidence: 87%
“…Food security and nutrition are major concerns in Nunatsiavut communities. As noted by Bowers et al (2020), a 2014 study found that 59.3% of the population was food insecure, while in the same year the same measurement Canadawide was 22%. According to Participant 8, some of the char bought by the Nunatsiavut Government is also traded with fishers in southern Labrador for Atlantic cod, which gives the community freezer program some variety.…”
Section: Food Security and Food Sovereigntymentioning
confidence: 87%
“…We chose these methods to ensure the sample could provide "the type of knowledge necessary to understand structures and processes of local context" (28). We identi ed 17 potential participants through purposeful sampling from a previous study (29) that identi ed policies that pertained to food security in Nunatsiavut. Five additional potential participants were identi ed through snowball sampling.…”
Section: Participant Selection and Recruitmentmentioning
confidence: 99%